A tri-dimensional conceptual framework of Chinese Buddhism-based death acceptance: Implications for gerontological practice - Xu, Jianbin (Journal of religion, spirituality & aging, 2025)
Building on Wong et al.’s (1994) tripartite model of death acceptance, this article aims to construct a tri-dimensional conceptual framework of Chinese Buddhism-based death acceptance. The conceptual framework argues that Chinese Buddhism has the potential to facilitate escape acceptance, neutral acceptance, and approach acceptance of death. First, the notion of duḥkha (suffering) can contribute to escape acceptance. Second, the doctrines of anitya (impermanence), pratītyasamutpāda (dependent origination), saṃsāra (the endless cycle of birth, death, and rebirth), and advaya (the life-death nonduality) would foster neutral acceptance. Third, the hopeful vision of a benign and blessed form of existence after death may promote approach acceptance. This conceptual framework can serve as a frame of reference for gerontological practitioners to empower elderly believers of Chinese Buddhism to accept death, address death-related concerns, and manage suicidal crisis (if any).